Pediatric Stomach and Duodenal Imaging - SK, Pritviraj; Kandasamy, Devasenathipathy; Jana, Manisha; Sharma, Raju; Gupta, Arun Kumar (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Pediatric stomach and duodenum abnormalities constitute a unique spectrum of conditions unlike adults which are categorized broadly into congenital, inflammatory, neoplastic and miscellaneous conditions. The aim of this article is to describe the role of imaging modalities in gastric and duodenal pathology in children. Some of the entities are unique to this age group and their imaging findings are also highlighted.
Keywords: pediatric; gastrointestinal; radiograph; ultrasound; CT/MRI